Scoping 'sex' and 'gender' in rehabilitation: (mis)representations and effects - Jessica Ott; Sarah N. Champagne; Abdulgafoor M. Bachani; Rosemary Morgan (BMC, 2022)
Abstract Background Researchers have highlighted a large-scale global unmet need for rehabilitation. While sex and gender have been shown to interact with each other and with other social and structural factors to influence health and wellbeing, less is known about how sex and gender shape rehabilitation participation and outcomes within health systems. Methods Using an intersectional approach, we examine literature that explores the relationship between sex and/or gender and rehabilitation access, use, adherence, outcomes, and caregiving. Following a comprehensive search, 65 documents met the inclusion criteria for this scoping review of published literature. Articles were coded for rehabilitation-related themes and categorized by type of rehabilitation, setting, and age of participants, to explore how existing literature aligned with documented global rehabilitation needs. Responding to a common conflation of sex and gender in the existing literature and a frequent misrepresentation of sex and gender as binary, the researchers also developed a schema to determine whether existing literature accurately represented sex and gender. Results The literature generally described worse rehabilitation access, use, adherence, and outcomes and a higher caregiving burden for conditions with rehabilitation needs among women than men. It also highlighted the interacting effects of social and structural factors like socioeconomic status, racial or ethnic identity, lack of referral, and inadequate insurance on rehabilitation participation and outcomes. However, existing literature on gender and rehabilitation has focused disproportionately on a few types of rehabilitation among adults in high-income country contexts and does not correspond with global geographic or condition-based rehabilitation needs. Furthermore, no articles were determined to have provided an apt depiction of sex and gender. Conclusion This review highlights a gap in global knowledge about the relationship between sex and/or gender and rehabilitation participation and outcomes within health systems. Future research should rely on social science and intersectional approaches to elucidate how gender and other social norms, roles, and structures influence a gender disparity in rehabilitation participation and outcomes. Health systems should prioritize person-centered, gender-responsive care, which involves delivering services that are responsive to the complex social norms, roles, and structures that intersect to shape gender inequitable rehabilitation participation and outcomes in diverse contexts.